A mu SR study of the magnetism in Prussian Blue analogue photomagnets - Salman, Z; Parolin, T; Chow, K; Keeler, T; Miller, R; Wang, D; Chakhalian, J; MacFarlane, W (2006)
In this work we present longitudinal field mu SR results in the molecular magnetic Co-Fe Prussian Blue analogue Rb1-2xCo1+x[Fe(CN)(6)] center dot zH(2)O, with x approximate to 0.17 which exhibits light induced magnetic ordering. We were unable to observe the effect of light with mu SR, but in the reportedly paramagnetic unilluminated state, we find evidence for glassy magnetic freezing. (c) 2005 Elsevier B.V. All rights reserved.